Faecal carriage of extended-spectrum β- lactamase producing Escherichia coli among undergraduate health sciences students of institute of medicine, Tribhuvan university teaching hospital. - Sharma, Birat
ABSTRACT: Background: Microorganism that are commonly found on or in body sites of healthy persons are called normal flora. The normal floras of the GI tract are commonly Gram Negative Bacteriodes and Enterobacteriaceae. ESBLs are B-lactamases that hydrolyse extended spectrum Cephalosporins. This study is designed to find the faecal carriage rate of ESBL producing E. coli among healthy medical students. Methodology: Total 156 faecal samples were collected from healthy medical students. All the samples were cultured in MacConkey Agar plates. The E. coli isolated from the culture were tested for ESBL production and Multi Drug Resistance were also confirmed. Result: Among the 156 stool samples of the healthy students, the ESBL producing E. coli were found among 18 of the samples and MDR E. coli were found among 23 of the samples. 11.5%of the total students were found to be the carries of ESBL producing E. coli whereas 14.7% of the total students were found to be the carriers of MDR E. coli. Conclusion: The ESBL carriage rate was not affected by the gender of the person. The incidence of ESBL carriage increases as the study year increases this means that more of the students are becoming the carries as the time of hospital exposure increases as the study year increases. Even the carriage rate of ESBL is higher among the students who get exposed to the hospital facilities almost daily as per their study program requires. Medical students during their posting are exposed to different patients who are infected or colonized by ESBL producers or MDR bacteria, the result of this is the students might get infected or be carries of the ESBL producing bacteria. Keywords: ESBL, MDR, E. Coli, Faecal Carriers, Normal Flora